2014
DOI: 10.1038/ncomms6322
|View full text |Cite
|
Sign up to set email alerts
|

Multiple enzymatic activities of ParB/Srx superfamily mediate sexual conflict among conjugative plasmids

Abstract: Conjugative plasmids are typically locked in intergenomic and sexual conflicts with coresident rivals, whose translocation they block using fertility inhibition factors (FINs). We describe here the first crystal structure of an enigmatic FIN Osa deployed by the proteobacterial plasmid pSa. Osa contains a catalytically active version of the ParB/Sulfiredoxin fold with both ATPase and DNase activity, the latter being regulated by an ATP-dependent switch. Using the Agrobacterium tumefaciens VirB/D4 type-IV secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 72 publications
0
30
0
Order By: Relevance
“…Oncogenic suppressive activity or ‘Osa’ protein is probably a connecting link between ParB and Srx. Osa contains both DNAse [18] of ParB as well as ATPase domain of Srx [28]. In normal human tissues, Srx is present in kidney, lungs, and pancreas [29].…”
Section: Introductionmentioning
confidence: 99%
“…Oncogenic suppressive activity or ‘Osa’ protein is probably a connecting link between ParB and Srx. Osa contains both DNAse [18] of ParB as well as ATPase domain of Srx [28]. In normal human tissues, Srx is present in kidney, lungs, and pancreas [29].…”
Section: Introductionmentioning
confidence: 99%
“…). In addition to their involvement in DNA PT modification, members of the ParB/Srx superfamily are observed in diverse biological processes: (i) ParB, a component of the plasmid‐partitioning system (Par), is essential in bacterial chromosome segregation during cell division (Schumacher and Funnell, ; Chen et al ., ); (ii) Srx, a sulfinic acid reductase in eukaryotes, is functionally unrelated to ParB but is suggested to originate via truncation of ParB (Basu and Koonin, ; Jonsson et al ., ); (iii) Osa, the fertility inhibition protein, blocks T‐DNA transfer into plants (Maindola et al ., ); and (iv) some polymorphic toxin systems were found to fuse C‐terminally with ParB domains and likely function as nucleases (Zhang et al ., ). Notably, the highly conserved DGQHR motif in DndB consistently aligns well with the signature sequence of G(E/C)(R/H)RxxA (x represents any residue) in ParBs and Srxs (Fig. )…”
Section: Resultsmentioning
confidence: 99%
“…(Basu and Koonin, ). Further structural modeling of DndB using the Phyre2 server (http://www.sbg.bio.ic.ac.uk/~phyre/) showed that DndB residues G114 and R117 in the D 113 GQHR 117 motif correspond well to the active site residues in the ATP‐binding pockets of Srx (G97, R101) and Osa (G137, R140) (Maindola et al ., ), prompting us to test if these conserved sites might also support the ATPase activity of DndB (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…This fold has been described in a functionally diverse ParB/Srx superfamily of proteins. Members are found in varied biological contexts and thus far are described to bind a nucleotide for kinase, ATPase, or DNase activity (32,36). To our knowledge, no ParB/Srx family member has been found to be directly involved in siderophore biosynthesis.…”
Section: Structure Determination Of Sbnimentioning
confidence: 99%
“…SerK is a free serine kinase from T. kodakarensis that uses ADP to phosphorylate L-serine to generate OPS for cysteine biosynthesis. Of the proteins annotated in the ParB/Srx family, SerK is the only identified kinase, although Osa and Srx both possess ATPase activity (36,40). Overall, the structures of SerK The overall fold of SbnI(1-240) is shown as a schematic and divided into two domains with N and C termini and ␣-helices labeled.…”
Section: Structure Determination Of Sbnimentioning
confidence: 99%